Urgensi Integrasi Pengaturan Mekanisme Keadilan Restoratif dalam Sistem Peradilan Pidana di Indonesia - Rahma, Nabila Aulia; Toloh, Pascal (UI Scholars Hub, 2022)
Conventional criminal law has always been synonymous with prison, where the settlement can result in the exclusion of the right to a sense of justice for victims because of their disproportionate position. This situation encourages the emergence of the concept of restorative justice, where based on this concept, criminal cases are resolved by involving perpetrators, communities and victims. However, at the regulatory level, the concept of restorative justice is set differently in various rules, which have not been synchronized, such as the internal rules of the Indonesian Police, the Attorney General's Office and the Supreme Court. Inconsistencies in these norms can have an impact on the level of implementation that is not in line with the formulation of an integrated criminal justice system or